Fiber Optics Technology and Applications - Huerta-Cuellar, Guillermo (IntechOpen, 2021)
The importance and necessity of communications systems have become evident during the COVID-19 pandemic. The development of new technologies that permit the best performance of these systems is paramount, and optical fibers play an important role in this area. This book examines new technological developments to improve optical fiber technology, with applications in communications systems, optoelectronics integration, and the scientific study of live microorganisms such as bacteria, viruses, fungi, and protozoa.